DETERMINATION OF ANTIBODIES AGAINST RETICULOENDOTHELIOSIS VIRUS IN LAYER HENS BY THE ELISA TEST - Grados T., Melina (2009)
The objective of this study was to evaluate the presence of antibodies against Reticuloendotheliosis virus (REV) in flocks of layers hens using commercial ELISA kits. A total of 630 serum samples from 42 flocks in production of 28 commercial farms in the department of La Libertad and the province of Lima were collected from July 2004 till March 2005. The results indicated that 33.3% (14/42) flocks were seropositive [22.2% (6/27) in Lima and 53.3% (8/15) in La Libertad respectively], and without significant association between the infection and history of tumor problems, age, and genetic line. This is the first study conducted in commercial layer hens and the results showed the presence of the REV in Peru.